PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS “PAPI PROTOTUM” SEBAGAI INOVASI PEMBELAJARAN PADA MATERI PROSES FOTOSINTESIS TUMBUHAN UNTUK SISWA KELAS 4 SDN KRATON - Natalia, Sofia; Mukmin, Bagus Amirul; Putri, Kharisma Eka (Information Technology Education Department, 2025)
This study aims to: (1) How is the validity of interactive multimedia based on papi prototum on the material of plant photosynthesis process (2) How is the practicality of interactive multimedia based on papi prototum on the material of plant photosynthesis process. The study was conducted on 17 students of grade IV of SDN Kraton. This study used the Research and Development (R&D) model with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) approach. The media development process was carried out systematically according to the ADDIE stages to produce valid, practical and effective learning media. The results of the three aspects obtained a result of 90.5% which is included in the